Studi Korelasi Obesitas dengan Kejadian Hipertensi Pada Wanita Usia 40 - 60 Tahun di Desa Kertosari Kecamatan Asembagus Kabupaten Situbondo - Muarrofah (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2009)
The result from this research shows out of 30 women responders most of suffering obesity 1 but doesn’t suffer hypertension 11 (33,67%) and partly small or there is no responders experiences obesity 1 with weight hypertension, obesity 1 with hypertension maligna, obesity 11 with hypertension maligna, hardly obesity with hypertension maligna, each them has frequency